Basic science breaks through: New therapeutic advances in Parkinson's disease. Issue 11 (16th July 2015) - Brundin, Patrik; Atkin, Graham; Lamberts, Jennifer T.
Abstract: Parkinson's disease (PD) is the second most common neurodegenerative disease and is typically associated with progressive motor dysfunction, although PD patients also exhibit a variety of non‐motor symptoms. The neuropathological hallmark of PD is intraneuronal inclusions containing primarily α‐Synuclein (α‐Syn), and several lines of evidence point to α‐Syn as a key contributor to disease progression. Thus, basic research in the field of PD is largely focused on understanding the pathogenic properties of α‐Syn. Over the past 2 y, these studies helped to identify several novel therapeutic strategies that have the potential to slow PD progression; such strategies include sequestration of extracellular α‐Syn through immunotherapy, reduction of α‐Syn multimerization or intracellular toxicity, and attenuation of the neuroinflammatory response. This review describes these and other putative therapeutic strategies, together with the basic science research that led to their identification. The current breadth of novel targets for the treatment of PD warrants cautious optimism in the fight against this devastating disease. © 2015 International Parkinson and Movement Disorder Society